Bioinspired design of AgNPs embedded silk sericin-based sponges for efficiently combating bacteria and promoting wound healing. (15th October 2019) - Tao, Gang; Cai, Rui; Wang, Yejing; Liu, Liying; Zuo, Hua; Zhao, Ping; Umar, Ahmad; Mao, Chuanbin; Xia, Qingyou; He, Huawei
Abstract: A wound dressing with excellent hydrophilicity, high porosity, good mechanical property, and antimicrobial activities holds great potential for wound healing. Sericin, a natural protein from silkworm cocoon, is particularly attractive for the development of skin-repairing materials because it is biocompatible and biodegradable. Here, we reported a green strategy for in situ biomimetic synthesis of silver nanoparticles (AgNPs) within sericin/poly(vinyl alcohol) hydrogel. AgNPs were in situ synthesized by the redox property of tyrosine residues in sericin without additional chemicals, similar to a biomineralization process. AgNPs-sericin/poly(vinyl alcohol) dressing was demonstrated to bear desired high porosity, good wettability, hygroscopicity, and mechanical properties. The evaluation of cytocompatibility and immunotoxicity of the composite with NIH/3T3, HEK-293, and RAW264.7 cells further demonstrated its excellent biocompatibility. The composite also showed an effective antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, and could inhibit biofilm formation caused by Staphylococcus aureus and Pseudomonas aeruginosa . Finally, the animal experiment suggested that the composite dressing could facilitate re-epithelialization and collagen deposition to promote wound healing. Our work shows that the composite dressing has great potential as a competitive alternative for traditional wound dressings. Graphical abstract: Unlabelled Image Highlights: AgNPs are synthesized by tyrosine of sericin, and embedded in the sericin-based sponge in a biomineralization manner. SP-Ag composite has desired mechanical properties, effective antibacterial activity and excellent cytocompatibility. SP-Ag composite could facilitate collagen deposition and promote wound healing.